The persisted effects of low-frequency repetitive transcranial magnetic stimulation to augment task-specific induced hand recovery following subacute stroke: Extended study - Tretriluxana, Jarugool; Thanakamchokchai, Jenjira; Jalayondeja, Chutima; Pakaprot, Narawut; Tretriluxana, Suradej (My University, 2018)
Objective To examine the long-term effects of the low-frequency repetitive transcranial magnetic stimulation (LFrTMS) combined with task-specific training on paretic hand function following subacute stroke. Methods Sixteen participants were randomly selected and grouped into two: the experimental group (real LFrTMS) and the control group (sham LF-rTMS). All the 16 participants were then taken through a 1-hour taskspecific training of the paretic hand. The corticospinal excitability (motor evoke potential [MEP] amplitude) of the non-lesioned hemisphere, and the paretic hand performance (Wolf Motor Function Test total movement time [WMFT-TMT]) were evaluated at baseline, after the LF-rTMS, immediately after task-specific training, 1 and 2 weeks after the training. Results Groups comparisons showed a significant difference in the MEP after LF-rTMS and after the training. Compared to the baseline, the MEP of the experimental group significantly decreased after LF-rTMS and after the training and that effect was maintained for 2 weeks. Group comparisons showed significant difference in WMFT-TMT after the training. Only in the experimental group, the WMFT-TMT of the can lifting item significantly reduced compared to the baseline and the effect was sustained for 2 weeks. Conclusion The results of this study established that the improvement in paretic hand after task-specific training was enhanced by LF-rTMS and it persisted for at least 2 weeks.
Keywords: Brain stimulation; Hand function; Neural plasticity; Stroke; Task-specific training